Effect of a high vs. standard dose of vitamin D3 supplementation on bone metabolism and kidney function in children with chronic kidney disease - Feng, Zhiqiang; Lu, Kunna; Ma, Yan; Liu, Feng; Zhang, Xinhuan; Li, Hongxiang; Fu, Yan (Frontiers in Pediatrics, 2022)
We investigated the effects of high- vs. standard-dose vitamin D supplementation on kidney function and bone metabolism in children with chronic kidney disease (CKD). Children were randomized to receive one of two formulations: 75 participants received 2,000 IU/D of oral supplementation of vitamin D, while 75 participants received 400 IU/d for a minimum of 4 months. We investigated the effects of vitamin D supplementation on kidney-related indicators and bone metabolism-related indicators at different doses. A total of 158 participants were screened, among whom 150 met the inclusion criteria. The indicators of chronic kidney disease such as eGFR and serum uric acid were negatively correlated with the 25(OH)D level and BMD. Serum 25(OH)D and osteocalcin levels were positively correlated with spine BMD. The standard dose of vitamin D can improve the serum uric acid level, but high doses of vitamin D supplementation had no significant effect on the serum uric acid level. High doses of vitamin D supplementation can also improve the alkaline phosphatase level. When comparing the results of different doses of vitamin D supplementation, it was found that high-dose vitamin D supplementation did not improve bone density in the spine and femur neck relative to the standard dose of vitamin D but improved hypocalcemia and N-terminal propeptide of the human procollagen type I (PINP) level. Among the children with clinical kidney disease, high-dose vitamin D treatment for 4 months resulted in statistically significant improvement in kidney function but no significant difference in bone metabolism compared with the standard-dose vitamin D treatment.